Spatial and temporal variations in stable isotope signatures (δ13C and δ15N) of the gammarids and the common carp in the southern coast of the Caspian Sea - Hajizadeh Koupayeh, Nazila (2020)
Despite the growing body of research on the use of stable isotope analysis in food web studies, spatial and temporal variations in stable isotope ratios of coastal communities are still poorly understood. The aim of my study is to explore how carbon and nitrogen stable isotopes of selected benthic communities vary spatially and temporally across the south of Caspian Sea. I followed carbon stable isotope ratios (δ13C) and nitrogen stable isotope ratios (δ15N) of gammarids and common carp (Cyprinus carpio) in four sites (Anzali, Noshahr, Sari, and Gomishan) from the southwest to the southeast of the Caspian Sea during May-November 2019 to address the following questions: 1) how do carbon and nitrogen stable isotope ratios of gammarids and carps change along the coastline in different months? 2) How do trophic levels of gammarids and carps vary spatially and temporally? My results revealed that there are spatial and temporal variations in stable isotope signatures of the gammarids and carps in the southern coast of the Caspian Sea, although month or site effects were not significant in some cases. Trophic position of gammarids and common carps varied among sites but was independent of month. On average, the amphipod Pontogammarus maeoticus in Noshahr presented the highest and the amphipod Gammarus aequicauda in Gomishan showed the lowest nitrogen stable isotope ratios among sites. Enrichment of δ13C in gammarids was the highest in Gomishan, followed by Sari, Noshahr and Anzali. There was an increasing trend in carbon stable isotope ratios of P. maeoticus from May to November in Sari, Noshahr and Anzali sites. Among sites, Gammarids in Anzali had the highest C:N ratios. There was a decreasing trend in C:N ratios of P. maeoticus from June-November in Anzali, Noshahr, and Sari sites. Carps in Noshahr enriched more with δ15N than those in other sites. Carps in Gomishan had the highest value of δ13C among all sites. Gammarids displayed the lowest trophic level in Gomishan among sites and a similar trophic level between Anzali and Sari. Gammarids in Noshahr showed significantly higher trophic level than those in Sari and Anzali. Among sites, C. carpio exhibited the highest trophic level in Noshahr. Allochthonous and autochthonous organic matters, sewage discharge, aquaculture wastes, agricultural fertilizers, Chl a concentrations, food quality, amount of lipids, and high degree of trophic variation were discussed as potential reasons for the observed spatial and temporal variation in stable isotope signatures of the gammarids and the carps. Results from this study indicated that low quality allochthonous organic matter originated from the rivers that flow into the Caspian Sea playing an important role in food web and ecosystem function of Caspian Sea. This study notifies water managers to set up proper and timely measures to mediate anthropogenic stressors and rehabilitation of fish spawning habitats.